Modeling expert judgment to assess cost-effectiveness of EU Marine Strategy Framework Directive programs of measures. (December 2015) - Kontogianni, A.; Tourkolias, C.; Damigos, D.; Skourtos, M.; Zanou, B.
Abstract: The EU Marine Strategy Framework Directive (MSFD) requires all Member States to establish a program of measures to achieve or maintain Good Environmental Status (GES) of their marine waters, which should be justified on economic grounds. So far, however, only limited efforts exist to support, from a scientific perspective, marine policy- and decision-makers to this direction. This paper describes a first effort towards closing this gap and improving existing marine policymaking processes as regards the prioritization and selection of measures and policies towards coastal and marine resources management. More specifically, the paper presents an expert judgment-based weighting framework named ' MeTaLi '. The tool provides a cost-effectiveness ranking algorithm of alternative measures (e.g. command-and-control, economic, etc.) within the framework of MSFD by means of fuzzy and stochastic analysis. A pilot application of ' MeTaLi ' in Greece for three selected MSFD descriptors is also discussed, aiming to evaluate the tool and allow drawing conclusions for real conditions. Finally, the paper concludes with a discussion of research findings and methodological challenges related to marine policy issues.